Analysis Key Variables and Generation Z Turnover Intention Scenarios: MICMAC and Bayesian Network Approaches - Nami, Ni Putu Shernita; Prianthara, Ida Bagus Teddy (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
Generation Z is projected to dominate the workforce and have great opportunities for the development of a company, but problems arise when various surveys show that Gen Z has a tendency to change jobs (turnover intention). This research aims to analyze key variables and explore shared Gen Z turnover intention scenarios. This research uses a new approach, namely MICMAC and Bayesian Belief Network (BBN. The research highlights that Gen Z employees’ turnover intentions are influenced by factors such as Job Insecurity, Job Stress, Compensation and Benefits, Job Satisfaction, and Leadership and Management, which can be anchored to the Two-Factor Theory and Equity Theory. The results of the strength analysis show that the probability of Gen Z turnover intention is 68%. Based on scenario analysis, it is proven that when Gen Z does not experience job stress, they do not experience job insecurity, and satisfaction with current work can reduce turnover intention levels by 40%. Reducing turnover intention will also have a positive impact on company stability, increasing by 29%. The findings of this research have significant implications for policy recommendations and practices in company management. This study emphasizes the importance of creating a supportive company environment to reduce job stress and job insecurity. Flexible policies and management support can create a positive work atmosphere, increase employee satisfaction, and reduce the risk of burnout.